Psychedelic Telepathy: An Interview Study - Johnstad, Petter Grahl (Journal of Scientific Exploration, 2020)
This article presents an interview study of telepathic experiences induced by psychedelic drugs, with the aim of broadening our understanding of the nature and characteristics of such experiences. Of 40 psychedelics users interviewed about their experiences, 16 reported some form of psychedelic telepathy. Respondents were recruited at various online fora for individual interviews via private messaging. They reported three main types of telepathic communication: 1) an information-exchange type of telepathy that often enabled people to communicate in images as well as words; 2) a type sometimes referred to as telempathy that allowed for the direct exchange of feeling-states; 3) a state of self-dissolution and telepathic unity where one could not differentiate one’s own thoughts and feelings from those of the friend or partner. Some participants complained about the lack of privacy especially in the more intense forms of telepathic states, and were hesitant to repeat the experience, while others claimed they had become accustomed to such states and experienced them regularly. The article concludes that further studies are warranted, and suggests a research design for an experimental study of psychedelic telepathy. Keywords: psychedelic, interview, qualitative, telepathy, self-dissolution